OSU-2S/Sorafenib Synergistic Antitumor Combination against Hepatocellular Carcinoma: The Role of PKCδ/p53 - Omar, Hany A.; Tolba, Mai F.; Hung, Jui-Hsiang; Al-Tel, Taleb H. (Frontiers in Pharmacology, 2016)
Background: Sorafenib (Nexavar®) is an FDA-approved systemic therapy for advanced hepatocellular carcinoma (HCC). However, the low efficacy and adverse effects at high doses limit the clinical application of sorafenib and strongly recommend its combination with other agents aiming at ameliorating its drawbacks. OSU-2S, a PKCδ activator, was selected as a potential candidate anticancer agent to be combined with sorafenib to promote the anti-cancer activity through synergistic interaction. Methods: The antitumor effects of sorafenib, OSU-2S and their combination were assessed by MTT assay, caspase activation, Western blotting, migration/invasion assays in four different HCC cell lines. The synergistic interactions were determined by Calcusyn analysis. PKCδ knockdown was used to elucidate the role of PKCδ activation as a mechanism for the synergy. The knockdown/over-expression of p53 was used to explain the differential sensitivity of HCC cell lines to sorafenib and/or OSU-2S. Results: OSU-2S synergistically enhanced the anti-proliferative effects of sorafenib in the four used HCC cell lines with combination indices < 1. This effect was accompanied by parallel increases in caspase 3/7 activity, PARP cleavage, PKCδ activation and HCC cell migration/invasion. In addition, PKCδ knockdown abolished the synergy between sorafenib and OSU-2S. Furthermore, p53 restoration in Hep3B cells through the over-expression rendered them more sensitive to both agents while p53 knockdown from HepG2 cells increased their resistance to both agents. Conclusions: OSU-2S augments the anti-proliferative effect of sorafenib in HCC cell lines, in part, through the activation of PKCδ. The p53 status in HCC cells predicts their sensitivity towards both sorafenib and OSU-2S. The proposed combination represents a therapeutically relevant approach that can lead to a new HCC therapeutic protocol.